Vertical distribution of 137Cs and natural radioactivity in core sediments of Thermaikos Gulf, northwestern Aegean Sea - Eleftheriou, G.; Tsabaris, C.; Philis-Tsirakis, E.; Kamberi, E.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
Sub-superficial sediments have been collected from the Thermaikos Gulf, located in the NW Aegean Sea, in order to determine sedimentation rates using vertical distributions of 137Cs and 210Pb. In addition measurements of the characteristic radionuclides of the 238U and 232Th natural series has also been performed to better understand the transport and the sedimentation process in a marine environment, which is strongly influenced by the main North Greece rivers. The sedimentation rates of the five selected cores using the two methods were consistent and varied from 0.20 ± 0.01 till 0.30 ± 0.02 cm y-1. The mean sedimentation rates derived with both methods are enhanced during the last ten years compared to previous values at the studied region by one order of magnitude, due to human implications. The activity concentration of the 238U decay products does not exhibit variation along the depth. The activities of 226Ra are enhanced ( 30 %) compared to the activities of radon daughters (214Pb, 214Bi) especially at the surface layer. The results of the correlation between 232Th decay products and 40K indicate that there is positive correlation between their averaged activities. The good proportionality between 232Th and 40K concentrations may be attributed to the fact that thorium is a particularly insoluble element in water.